Vancomycin Prescription Pattern in a Teaching Hospital: The Promising Role of Antimicrobial Control Programs - Mostafa Alavi-Moghadam; Farhad Shahim; Mohammad Sistanizad; Elham Pourheidar; Rezvan Hassanpour (Research Center for Rational Use of Drugs (RCRUD), 2020)
Background: Irrational consumption of antibiotics is one of healthcare problems and can lead to antibiotic resistance.vancomycin resistance be developing and has a huge cost burden to healthcare. Antimicrobial control programs is an essential strategy for optimal use of antibiotics and educational program is the main of these activities. Objective: This study was aimed to evaluate the effects of educational programon vancomycin prescription pattern. Methods: This pre-post interventional study was carried out between 2014 to 2016 in a university affiliated hospital,Tehran, Iran. In the first step, vancomycin usage protocol was prepared, then educational program delivered through workshops and physicians and assistants obligated to order vancomycin based on approved protocol. In the second step to assess the effectiveness of intervention, the prescription pattern of vancomycin assessed in Defined Daily Dose (DDD) per 100 patients days. Results: Vancomycin usage based on DDD per 100 patients days in post educational intervention period in comparison with period before intervention, December 2014 to March 2015, was decreased in all hospital departments but in comparison with three months period, September to December 2015, was decreased in all hospital departments with the exception of  intensive care department. Conclusion: Despite the efforts to reduce the excessive use of antibiotics, irrational consumption is a main concern.Educational program will improve the consumption of antibiotics. The present study showed the antimicrobial educational programs has been effective in the utilization of vancomycin in a university affiliated hospital. Keywords:Irrational use, Educational program, vancomycin prescription pattern.